Evaluation of lactic acid and blood pressure pre and post training in university students - Trujillo Chávez, Hugo Santiago (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: The modeling of sports training depends on the efficient control of various bioadaptative parameters related to cardiovascular potentiation and muscle lactation accumulation. The analysis of these indicators allows to establish the scope and limitations of the programs that implement physical loads to develop motor habits and skills. Objective: To evaluate the lactic acid and blood pressure levels in two moments of the teaching-educational preparation (Pre and Post training) in university students of the Escuela Superior Politécnica de Chimborazo. Methods: The study is descriptive and quasi-experimental, selecting a representative sample of university students (99 subjects), in both sexes. The lactic acid and blood pressure level were studied at rest and immediately after a sports training. Results: The average value of lactic acid at rest or pretest was 24.96 mg / dL, while the average value obtained at the second moment or posttest was 53.46 mg / dL. In the case of blood pressure, the resting average was set at 127/82 mmHg, and the average in excitation phase was 134/83 mmHg. Conclusions: An imbalance of normal lactate values at rest (High) and normal in excitation status is indicated. Blood pressure indices are established as normal at rest and excitement. In general, the physical loads applied to university students are adequate to levels required in specialized sports programs.